Comment on the paper “Lie group method for the modified model of MHD flow and heat transfer of a non-Newtonian fluid with prescribed heat flux over a moving porous plate, Xinhui Si, Lili Yuan, Liancun Zheng, Yanan Shen, Limei Cao, Journal of Molecular Liquids 220 (2016) 768–777” - Pantokratoras, Asterios (Journal of molecular liquids, 2019)
The present comment concerns some doubtful results included in the above paper. •The comment concerns a paper published in JML.•The slip parameter and the local Reynolds number are dimensional and wrong.•The local skin friction coefficient and the local Nusselt number are dimensional and wrong.